Gastrointestinal bleed induced by a fixed dose combination of rabeprazole and diclofenac sodium - Tandon, Vishal R. (Medknow Publications & Media Pvt Ltd, 2014)
Non-steroidal anti-inflammatory drugs (NSAIDs) are known to cause gastrointestinal (GI) bleed. Co-administration of proton pump inhibitors (PPIs) has been widely suggested as one of the strategies to prevent these GI complications among NSAIDs users. Herein, we present a case of severe GI bleeding in a patient taking fixed dose combination (FDC) of rabeprazole (20 mg) and diclofenac sodium (100 SR).